Heat and mass transfer effect on an infinite vertical plate in the presence of hall current and thermal radiation with variable temperature - Manjula, Lingala; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
MHD and radiated heat flow on a rotating system of an electrically conducting fluid in the presence of Hall current under the influence of variable temperature is studied analytically. An exact solution of a non-dimensional form of coupled partial differential equations is obtained by the technique of Laplace transform.
Keywords: MHD; Hall effects; radiation; vertical plate; variable temperature